1976
DOI: 10.1037/0022-3514.33.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Self-disclosure: An attributional perspective.

Abstract: This experiment examined the effect of timing of an intimate disclosure and assignment of responsibility for the event disclosed on interpersonal attraction. Subjects were induced to interact with a confederate who in all cases revealed something quite personal about himself. The disclosure occurred either early or near the end of a 10-minute conversation. The confederate accepted responsibility for the event disclosed, did not mention responsibility, or assigned responsibility to external factors. Negative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 8 publications
2
59
1
Order By: Relevance
“…The disclosure of more intimate information has a stronger effect on liking than disclosure of more generic, less intimate information (Collins & Miller, 1994;Levesque, Steciuk, & Ledley, 2002). Indeed recipients of intimate disclosures feel trusted, liked, and are more likely to evaluate the discloser positively (Wortman, Adesman, & Herman, 1976;Collins & Miller, 1994). Taken together, these studies provide some support for the idea that organizations may be able to improve co-worker relationships by offering opportunities to socialize and share personal information.…”
Section: Disclosure and Interpersonal Relationshipssupporting
confidence: 59%
“…The disclosure of more intimate information has a stronger effect on liking than disclosure of more generic, less intimate information (Collins & Miller, 1994;Levesque, Steciuk, & Ledley, 2002). Indeed recipients of intimate disclosures feel trusted, liked, and are more likely to evaluate the discloser positively (Wortman, Adesman, & Herman, 1976;Collins & Miller, 1994). Taken together, these studies provide some support for the idea that organizations may be able to improve co-worker relationships by offering opportunities to socialize and share personal information.…”
Section: Disclosure and Interpersonal Relationshipssupporting
confidence: 59%
“…According to Wortman, Adesman, Herman, and Greenberg (1976), a highly personal remark made early in a conversation will be attributed to the discloser's personality, whereas that same remark made late in the conversation is more likely to be taken as an indication of the discloser's liking and trust for the receiver, which in turn will enhance the receiver's liking for the discloser. Both Wortman et al (1976) and Archer and Burleson (1980) have found support for this position.In addition to the attribution approach, other theories in person perception may provide insights into self-disclosure phenomena. One approach that holds great promise in explaining self-disclosure behavior and has been virtually ignored is Anderson's (1974Anderson's ( , 1981 integration theory.…”
mentioning
confidence: 60%
“…High self-disclosure may be seen as an inappropriate attempt at ingratiation (Jones & Wortman, 1973;Kleinke, 1975, chap. 8), especially when it comes too early in an interaction (Jones & Gordon, 1972;Wortman et al, 1976). It would be interesting to know whether subjects in the present experiments gave negative evaluations to highly disclosing males because they perceived the males as being in an ingratiating situation (Kleinke, Staneski, & Weaver, 1972;Staneski, Kleinke, & Meeker, 1977).…”
Section: Discussionmentioning
confidence: 93%